Ultrasound Prenatal Diagnosis of Inguinal Scrotal Hernia and Contralateral Hydrocele. (11th December 2013) - Massaro, G.; Sglavo, G.; Cavallaro, A.; Pastore, G.; Nappi, C.; Di Carlo, C.
Abstract : Fetal inguinal scrotal hernia is a rare condition resulting in an abnormal embryonic process of the tunica vaginalis. We report a case of ultrasound prenatal diagnosis of inguinal scrotal hernia associated with contralateral hydrocele in a woman at 37 weeks of gestation, referred to our clinic for a scrotal mass. Differential diagnosis includes hydrocele, teratoma, hemangiomas, solid tumours of testis, bowel herniation, and testicular torsion. Bowel peristalsis is an important ultrasound sign and it allowed us to make diagnosis of inguinal scrotal hernia. Diagnosis was confirmed at birth and a laparoscopic hernia repair was performed without complications on day 10. During surgery, a bilateral defect of canal inguinal was seen and considered as the cause of scrotal inguinal hernia and contralateral hydrocele observed in utero.